Pan-Genome-Wide Analysis of Pantoea ananatis Identified Genes Linked to Pathogenicity in Onion - Agarwal, Gaurav; Choudhary, Divya; Stice, Shaun P.; Myers, Brendon K.; Gitaitis, Ronald D.; Venter, Stephanus N.; Kvitko, Brian H.; Dutta, Bhabesh (Frontiers in Microbiology, 2021)
Pantoea ananatis, a gram negative and facultative anaerobic bacterium is a member of a Pantoea spp. complex that causes center rot of onion, which significantly affects onion yield and quality. This pathogen does not have typical virulence factors like type II or type III secretion systems but appears to require a biosynthetic gene-cluster, HiVir/PASVIL (located chromosomally comprised of 14 genes), for a phosphonate secondary metabolite, and the ‘alt’ gene cluster (located in plasmid and comprised of 11 genes) that aids in bacterial colonization in onion bulbs by imparting tolerance to thiosulfinates. We conducted a deep pan-genome-wide association study (pan-GWAS) to predict additional genes associated with pathogenicity in P. ananatis using a panel of diverse strains (n = 81). We utilized a red-onion scale necrosis assay as an indicator of pathogenicity. Based on this assay, we differentiated pathogenic (n = 51)- vs. non-pathogenic (n = 30)-strains phenotypically. Pan-genome analysis revealed a large core genome of 3,153 genes and a flexible accessory genome. Pan-GWAS using the presence and absence variants (PAVs) predicted 42 genes, including 14 from the previously identified HiVir/PASVIL cluster associated with pathogenicity, and 28 novel genes that were not previously associated with pathogenicity in onion. Of the 28 novel genes identified, eight have annotated functions of site-specific tyrosine kinase, N-acetylmuramoyl-L-alanine amidase, conjugal transfer, and HTH-type transcriptional regulator. The remaining 20 genes are currently hypothetical. Further, a core-genome SNPs-based phylogeny and horizontal gene transfer (HGT) studies were also conducted to assess the extent of lateral gene transfer among diverse P. ananatis strains. Phylogenetic analysis based on PAVs and whole genome multi locus sequence typing (wgMLST) rather than core-genome SNPs distinguished red-scale necrosis inducing (pathogenic) strains from non-scale necrosis inducing (non-pathogenic) strains of P. ananatis. A total of 1182 HGT events including the HiVir/PASVIL and alt cluster genes were identified. These events could be regarded as a major contributing factor to the diversification, niche-adaptation and potential acquisition of pathogenicity/virulence genes in P. ananatis.